Bullae, Bronchiectasis and Nutritional Emphysema in Severe Anorexia Nervosa - Victoria J Cook; Harvey O Coxson; Andrew G Mason; Tony R Bai (Canadian Respiratory Journal)
STUDY OBJECTIVES: Pulmonary complications of anorexia nervosa are rarely documented. The case of a patient with anorexia nervosa and pulmonary disease is presented, a new quantitative computed tomography (CT) method for the detection of emphysema is employed, the literature is reviewed and the concept of 'nutritional' emphysema is discussed.